Assessing multi-climate-hazard threat in the coastal region of Bangladesh by combining influential environmental and anthropogenic factors. (December 2022) - Murshed, Sanzida; Griffin, Amy L.; Islam, Md Ashraful; Wang, Xiao Hua; Paull, David
Abstract: This study developed a geo-spatial framework for assessing multi-hazard threat on the Bangladesh coast, integrating environmental hazards (EH), geo-environmental attributes (GA), and anthropogenic modifications (AM) based on their potential contribution to overall threat. For this purpose, a fuzzy logic based analytical technique was integrated with geospatial mapping. Thematic layers were prepared for twenty-three theoretically important factors representing the three components of threat. The spatial variations of threat and its components were delineated through spatial overlaying of the respective layers in a GIS environment. The final threat map revealed 32% (5338 km 2 ) and 4% (646 km 2 ) of the area of the western deltaic coast, which encompassed >50–60% of the areas of Khulna, Bagerhat, and Satkhira districts, was under high and very high threat, respectively, owing primarily to frequent cyclones, salinity ingression, and subsidence, and secondarily to the low elevation of the coast, high astronomical tide, shallow bathymetry, excessive groundwater extraction, and polder construction. High and very high threat zones within the central estuarine coast corresponded to 27% (4518 km 2 ) and 16% (2618 km 2 ) of the area, including most of Bhola, Barguna, and Patuakhali districts, which was attributable to the effects of coastal erosion, sea-level rise, flooding and the ancillary effects of strong wave action, high river discharge, deforestation, and land transformation. Around 14% (948 km 2 ) and 3% (164 km 2 ) of the eastern cliff coast, comprising the southwestern part of the Coxsbazar district, was found to be under high and very high threat, respectively, due to the direct effects of sea-level rise, storm surge, erosion, and indirect effects of closeness to the shoreline, alluvial composition of the beach, tourism, and pollution from industries. The outcomes of this study could guide the coastal managers of Bangladesh in prioritizing actions aimed at disaster risk reduction and sustainable development of this region. Highlights: We assessed multi-climate-hazard coastal threats in Bangladesh using a geospatial approach. Environmental and anthropogenic factors were considered as compounding factors. Fuzzy-logic-based normalization and weighting of threat factors were applied. The findings showed good consistency with NIRAPAD's disaster impact index. The approach can inform prioritizing areas for immediate risk-reduction actions.